Psychopathy is a neglected public health problem - Chinchilla, Melanie A.; Reidy, Dennis E.; Kosson, David S. (Frontiers in Psychiatry, 2026)
Although psychopathy has been widely studied within criminal justice contexts, its impact on society is rarely considered in public health contexts. Even so, evidence strongly implicates psychopathic traits in substantial costs (not just fiscal) to society. Individuals with psychopathic features commonly hurt those with whom they have relationships in important ways, including through abuse, manipulation, deception and, often, violence. We review the empirical evidence linking psychopathic traits to three recognized public health problems: substance misuse, sexual risk behavior, and violence. We argue that the evidence suggesting robust links between psychopathic traits and these known public health problems warrant the recognition of psychopathy as a public health concern in its own right. We argue that failing to consider psychopathy through a public health lens will slow research progress and the development of prevention strategies. Implications for public policy are considered.